"Amorosa Contemplatione": Bernini, Bruni, and the Poetic Vision of Saint Teresa. Issue 2 (2nd April 2020) - Unglaub, Jonathan
Abstract : The interface between verbal and visual modes of artistic expression is demonstrated in the work of the poet Antonio Bruni and sculptor Gian Lorenzo Bernini. Bruni published verse on Apollo and Daphne and the bronze Urban VIII, epitomizing their poetic effects. Conversely, his ode on the transverberation of Saint Teresa by an angel creates a dramatic mise-en-scène that antecedes the amorous conceits, bodily forms, and celestial staging in Bernini's sculpture of the ecstatic mystic within the multimedia Cornaro Chapel. Both Bruni and Bernini exemplified a new poetica sacra, applying lyrical tropes to religious truth, presented vividly to the senses.